2022
DOI: 10.3390/jcm11030682
|View full text |Cite
|
Sign up to set email alerts
|

Non-Interventional Prospective Observational Study of Platelet Rich Fibrin as a Therapy Adjunctive in Patients with Medication-Related Osteonecrosis of the Jaw

Abstract: Background: Medication-related osteonecrosis (MRONJ) of the jaw is a severe and feared side effect of antiresorptive therapy in the oncological setting. With growing evidence that impaired angiogenesis may represent a key factor in pathogenesis, the aim of this study was to evaluate an autologous platelet concentrate as a possible additive in surgical therapy to optimize vascularization and, subsequently, resolution rates. Material and Methods: A non-interventional, prospective, multicenter study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…One of these studies, a randomized clinical trial, reported that it was not possible to establish the advantage of using P-PRF despite observing a short-term improvement in quality of life and a reduction in postoperative pain and infections 21 . However, a prospective observational study did not show significant improvement in terms of downstaging, pain sensation, and quality of life-related to oral health 22 . In three studies, the P-PRF was evaluated and indicated as a step in the prevention of osteonecrosis of the jaws related to the use of antiresorptive and antiangiogenic drugs in patients requiring extractions 23 , 24 , 25 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…One of these studies, a randomized clinical trial, reported that it was not possible to establish the advantage of using P-PRF despite observing a short-term improvement in quality of life and a reduction in postoperative pain and infections 21 . However, a prospective observational study did not show significant improvement in terms of downstaging, pain sensation, and quality of life-related to oral health 22 . In three studies, the P-PRF was evaluated and indicated as a step in the prevention of osteonecrosis of the jaws related to the use of antiresorptive and antiangiogenic drugs in patients requiring extractions 23 , 24 , 25 .…”
Section: Resultsmentioning
confidence: 86%
“…Eight studies used P-PRF as a platelet concentrate. Five studies evaluated the treatment for osteonecrosis of the mandible associated with bisphosphonates 18 , 19 , 20 , 21 , 22 , and two studies reported that it is not possible to prove the improvement in cases of osteonecrosis of the mandible with the use of this aggregating agent 21 , 22 . One of these studies, a randomized clinical trial, reported that it was not possible to establish the advantage of using P-PRF despite observing a short-term improvement in quality of life and a reduction in postoperative pain and infections 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of Piezoelectric in surgery is considered a less aggressive option and has been cited as a good choice in MRONJ cases [60,71]. To enhance surgical outcomes, various adjuvant therapies have been proposed in the literature, including parathyroid hormone (PTH), laser therapy, hyperbaric oxygen therapy, ozone therapy, and platelet-rich plasma (L-PRP/PRGF/PRP) [47,49,51,52,63,29,75]. These adjuvant therapies have shown faster and more comfortable postoperative healing.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend establishing or using a scale or index to evaluate wound healing. In a very comprehensive approach, Blatt et al [ 89 ] combined eight items, each measured on a 5-point scale (with 0 indicating the lowest and 5 the highest value of the item): wound size, depth, necrotic tissue type, total amount of necrotic tissue, granulation tissue type, total amount of granulation tissue, edges, and peri-ulcer skin/mucosa viability. In addition, pain and oral health-related quality of life were assessed.…”
Section: Discussionmentioning
confidence: 99%